Assessment of Location and Anatomical Characteristics of Mental Foramen, Anterior Loop and Mandibular Incisive Canal Using Cone Beam Computed Tomography - Mehrdad Panjnoush; Zonnar Sadat Rabiee; Yasaman Kheirandish (Tehran University of Medical Sciences, 2016)
Objectives: This study aimed to evaluate the location and characteristics of mental foramen, anterior loop and mandibular incisive canal using cone beam computed tomography (CBCT). Materials and Methods: This retrospective cross-sectional study evaluated 200 mandibular CBCT scans for the location of mental foramen, anterior loop prevalence and mandibular incisive canal visibility, its mean length and distance to buccal and lingual plates and inferior border of the mandible. The effect of age and gender on these variables was also analyzed (P<0.05). Results: Anterior loop and mandibular incisive canal were seen in 59.5% and 97.5% of the cases, respectively. The mean length of the mandibular incisive canal was 10.48±4.53mm in the right and 10.40±4.52mm in the left side. The mean distance from the endpoints of the canal to buccal plate was 3.63±1.73mm in the right and 3.66±1.45mm in the left side. These distances were 3.89±1.53mm in the right and 4.13±1.48mm in the left side to lingual plate and 9.98±2.07mm in the right and 8.62±1.97mm in the left side to the inferior border of the mandible. The distance from the endpoints of the canal to lingual plate was significantly different in the right and left sides. The distance from the endpoint of the canal to the buccal plate and inferior border of the mandible was significantly shorter in females (P=0.016), and had a weak, significant correlation with age (rsp=0.215, P=0.003). Conclusions: Due to variability in mandibular incisive canal length and high prevalence of anterior loop, CBCT is recommended before surgical manipulation of interforaminal region. Keywords: Anatomic Landmarks; Cone-Beam Computed Tomography; Mandible; Mandibular Nerve